KARAKTERISTIK FISIK EDIBLE FILM DENGAN VARIASI PEKTIN KULIT PISANG TANDUK DAN MINYAK ATSIRI CENGKEH - Sari, Myra Wardati; Nissa, Berta Khairun (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2021)
Banana plants have high production of fruit, this is compared straight about waste of banana peels. To overcome this problem, utilizing pectin of banana peel waste as an ingredient for making edible films. Clove essential oil can be used as additive in edible films as an antimicrobial that can inhibit food-destroying microorganisms. The purpose of this study was to determine the characteristics of the edible film of the pectin of the banana peel with the addition of clove essential oil with reference to the Japan Industrial Standard (JIS) Vol. 2: 1707. The method used in this research is banana peel pectin extraction, with variations in pectin concentration 0; 4; 6; 8 grams and clove essential oil 0.2; 0.4; 0.6 mL. The best edible film products that meet the JIS standard values ​​are sample B4 with a composition of 3 grams of pectin in banana peel and 0.6 mL of clove essential oil with a thickness value of 0.23 mm; the tensile strength value is 0.46 Mpa, the percent elongation is 48%, and the water vapor transmission rate (WVTR) is 6.78 g/m2/day. The appearance of the edible film produced is clear brown in color due to the influence of the color of banana peel pectin and clove essential oil. Based on these results, it can be concluded that the edible film produced meets the main parameter standards given by JIS which is used as a reference.